Intolerance of Uncertainty and Fear of Childbirth: Role of Perceived Preparedness for Childbirth - Maja Brekalo; Andela Kuljanac; Sandra Nakić Radoš (Clínica y Salud. Investigación Empírica en Psicología, 2024)

(untitled)
Background: Fear of childbirth (FOC) can lead to diverse adverse outcomes for pregnant women. Personality dispositions are one of the predictors of FOC, and intolerance of uncertainty is one of them. Previous studies were inconclusive, suggesting that intolerance of uncertainty was a predictor of FOC in pregnant women. However, the underlying mechanisms of that relation are still underexamined. Therefore, this cross-sectional study aimed to examine the mediation role of perceived preparedness for childbirth in the association between intolerance of uncertainty and FOC. Method: Participants were 168 primiparous pregnant and 124 multiparous pregnant women. Women fill out the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ), Intolerance of Uncertainty Scale (IUS), and a demographic sheet while waiting for regular prenatal checkup in hospital. Results: Results showed that perceived preparedness was a full mediator between intolerance of uncertainty and FOC in primiparous women. Intolerance of uncertainty was not correlated with FOC nor preparedness in multiparous women. Conclusions: Intolerance of uncertainty predicted FOC only indirectly through lower perceived preparedness for childbirth in primiparous women. Practical implications are discussed.